Development of a flexible dry electrode based MXene with low contact impedance for biopotential recording. (28th February 2022) - Peng, Hui-Ling; Sun, Yue-ling; Bi, Cheng; Li, Quan-Fu
Highlights: High conductive MXene (Ti3 C2 Tx ) was used. Fabricated a flexible dry electrode for biopotential recording. Investigated the relationship between contact impedances of the dry electrode and the quality of recording signals. The flexible dry electrode can record ECG, EEG, and EOG accurately as the standard electrode (Ag/AgCl electrode). Abstract: The dry electrode for biopotential recording is urgently need in wearable health monitoring systems, brain-computer interface (BCI), and human–computer interaction (HCI). However, high contact impedances of the electrode and the skin and inadequate shape adaptability of the electrode are challenges for the dry electrode to record signals accurately. Here, we present a flexible dry electrode based on transferring MXene (Ti3 C2 Tx ) ink on a flexible polyimide (PI) substrate for biopotential recording. The electrode exhibits low contact impedances and excellent flexibility to conform the skin well. In vivo biopotential recording demonstrated the flexible dry electrode can record electrocardiograms (ECG), electroencephalograms (EEG), and electrooculogram (EOG) as accurately as the standard electrode (Ag/AgCl electrode). Moreover, our electrode can record ECG accurately, even the subject is in motion. The flexible dry electrode is suitable for wearable biopotential recording and promising to be used in wearable health monitoring systems, BCI, and HCI.